The Effects of Salinity on the Filtration Rates of Juvenile Tropical Oyster Crassostrea iredalei - Geraldine Olive Ju Lien Chang; Lai Ven Inn; Aileen Tan Shau Hwai; Zulfigar Yasin (Tropical Life Sciences Research, 2016)
A small scale laboratory study was conducted to determine the effects of salinity ranging from 15, 20, 25, 30, 35, 40, and 45 ppt on the filtration rates of juvenile oyster Crassostrea iredalei with 25 ppt as the control. Three juvenile oysters (shell weight: 1.04 ± 0.12 g; shell length: 1.9 ± 0.2 cm; shell height: 1.9 ± 0.1 cm) were used to test the filtration rates in each salinity over the course of 8 hours. The hourly filtration rates were determined from the exponential decrease in algal (Chaetoceros calcitrans) concentration as a function of time. The oyster in 35 ppt salinity produced the highest overall filtration rate (FR2) with 134.06 ± 15.66 mL–1 hr–1 oyster–1 and the lowest overall filtration rate (FR2) occurred in oyster exposed to 15 ppt and 45 ppt with 31.30 ± 6.90 mL–1 hr–1 oyster–1 and 32.11 ± 7.68 mL–1 hr–1 oyster–1 respectively throughout the 8 hours. The result from this study can be useful for optimum oyster culturing and the oysters can be employed as a natural biofilter in marine polyculture farming.